Issues in location-based multicast routing in manets - Qabajeh, Mohammad M.; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Qabajeh, Liana K. (IIUM Press, 2011)
Mobile Ad Hoc Networks (MANETs) are an autonomous system of a set of mobile nodes connected by shared wireless links, forming a temporary network without relying on any infrastructure. MANETs characteristics include self-organizing, self-configuring, multihop communication, continuous mobility and strict resource limitation. These characteristics coupled with the characteristics of the wireless communication medium make routing protocols one of the major issues to consider in MANETs